Analysis of the Implementation of Women's Empowerment Programs Through Home Industries Using George C. Edwards III's Approach in Ternate City - Musdalifah Musdalifah (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This study analyzes the implementation of a women's empowerment policy through home industry programs by the Office of Women’s Empowerment and Child Protection (DP3A) in Ternate City. Employing a descriptive qualitative approach and George C. Edwards III’s policy implementation theory, the study focuses on four dimensions: communication, resources, disposition, and bureaucratic structure. The findings reveal that policy execution remains suboptimal. Communication tends to be one-directional, resource limitations persist, and inter-agency coordination is lacking. While implementers show strong commitment, fragmented bureaucracy hinders effective outcomes. The program is grounded in legal frameworks such as Regulation of the Minister of Women’s Empowerment No. 2/2016 and regional regulations issued by the Ternate City Government. This research highlights the need for enhanced two-way communication, inter-sectoral synergy, and capacity-building to ensure successful and sustainable local-level women’s empowerment initiatives.